Urolithin A attenuated ox-LDL-induced cholesterol accumulation in macrophages partly through regulating miR-33a and ERK/AMPK/SREBP1 signaling pathways. Issue 4 (1st April 2020) - Han, Qi-an; Su, Dongfang; Shi, Chao; Liu, Peifeng; Wang, Yue; Zhu, Beiwei; Xia, Xiaodong
Abstract : Urolithin A attenuated cholesterol accumulation in macrophage cells possibly through interaction with ERK/AMPKα/SREBP1 signaling pathways and regulation of miR-33a expression. Abstract : Promoting cholesterol efflux from foam cells represents one of the therapeutic strategies for ameliorating atherosclerosis. Urolithin A (UA) has been shown before to attenuate ox-LDL induced endothelial dysfunction in endothelial cells with its anti-inflammatory properties. The aim of this study was to investigate whether UA could promote cholesterol efflux via modulating related microRNA (miR) and signaling pathways. RAW264.7 cells were treated with 50 μg mL −1 ox-LDL to induce foam cell formation. After treatment with UA at different concentrations, intercellular and extracellular cholesterol levels were determined. Expression of Erk1/2, AMPKα and their phosphorylation forms, and SREBP1, was analyzed by western-blotting. The effect of UA on miR-33a expression and the involvement of miR-33a in cholesterol efflux regulation were also investigated. UA reduced ox-LDL induced cholesterol accumulation in macrophage cells and promoted cholesterol efflux from cells. Compared with ox-LDL treated cells, UA treatment reduced the level of phosphorylated ERK1/2, increased the expression of phosphorylated AMPKα and decreased the SREBP1 expression. Moreover, UA decreased the miR-33a expression at the transcriptional level but increased the transcriptional expression of ATP-binding cassette transporter A1 (ABCA1) and ABCG1, two genes contributing to reverse cholesterol transport. Furthermore, pre-miR-33a attenuated cholesterol efflux induced by UA. Collectively, UA promoted the reverse cholesterol transport in macrophage-derived foam cells and interfered with cholesterol metabolism possibly through regulating the miRNA-33 expression and interaction with the ERK/AMPKα/SREBP1 signaling pathway.